Multimodality Imaging Features of a Misleading Sacral Giant Cell Tumor in 18F-FDG PET/CT, Bone Scan, and MRI. (October 2020) - Dejust, Sebastien; Jallerat, Pascaline; Soibinet-Oudot, Pauline; Jouannaud, Christelle; Morland, David
Abstract : Abstract: We report the case of an asymptomatic 66-year-old woman referred for initial staging of an invasive ductal breast carcinoma. Initial workup incidentally revealed a bone tumor of right sacral wing corresponding to a giant cell tumor (GCT). We present the imaging characteristics of GCT on 99m Tc-HDP bone scan (doughnut sign), 18 F-FDG PET/CT (intense and heterogeneous uptake of a prominent geographic lytic lesion with partial rupture of cortical), and MRI (hyposignal with gadolinium enhancement on T1-weighted images and heterogeneous hypersignal on T2-weighted images). GCT is a benign but locally aggressive primary bone tumor, constituting a pitfall and diagnostic challenge.